The lysosomal transporter MFSD1 is essential for liver homeostasis and critically depends on its accessory subunit GLMP - Massa Lopez, David; Thelen, Melanie; Stahl, Felix; Thiel, Christian; Linhorst, Arne; Sylvester, Marc; Hermanns-Borgmeyer, Irm; Lüllmann-Rauch, Renate; Eskild, Winnie; Saftig, Paul; Damme, Markus (eLife, 2019)
Lysosomes are major sites for intracellular, acidic hydrolase-mediated proteolysis and cellular degradation. The export of low-molecular-weight catabolic end-products is facilitated by polytopic transmembrane proteins mediating secondary active or passive transport. A number of these lysosomal transporters, however, remain enigmatic. We present a detailed analysis of MFSD1, a hitherto uncharacterized lysosomal family member of the major facilitator superfamily. MFSD1 is not N-glycosylated. It contains a dileucine-based sorting motif needed for its transport to lysosomes. Mfsd1 knockout mice develop splenomegaly and severe liver disease. Proteomics of isolated lysosomes from Mfsd1 knockout mice revealed GLMP as a critical accessory subunit for MFSD1. MFSD1 and GLMP physically interact. GLMP is essential for the maintenance of normal levels of MFSD1 in lysosomes and vice versa. Glmp knockout mice mimic the phenotype of Mfsd1 knockout mice. Our data reveal a tightly linked MFSD1/GLMP lysosomal membrane protein transporter complex.
Gesehen am 15.06.2020